ANALISIS PENGARUH REPUTASI PERUSAHAAN SHOPEE PASCA GELOMBANG PHK TERHADAP MINAT PEMBELIAN : Survei pada Konsumen di Jabodetabek - Clara Kristi Siagian (2023)
This research aims to examine the influence of Shopee's reputation after the wave of layoffs on consumer purchasing intention in the Jabodetabek region. The theory aligned with this research is the Corporate Reputation Theory. The method used in this study is a quantitative method. The research population consists of Shopee consumer community with a sample size of 100 respondents. The findings indicate a strong positive correlation between Shopee's Corporate Reputation after the wave of layoffs and consumer purchasing intention. These results are supported by the Hypothesis Test, which shows that H0 is rejected and Ha is accepted, meaning that corporate reputation influences consumer purchasing intention. The results are in line with the Corporate Reputation Theory. It is evident that the reputation established by Shopee from the beginning is deeply ingrained in the minds of consumers, so even during the mass layoffs, consumer buying interest remains high. Reputation is an important aspect for companies to build, as it creates a positive image in the middle of public.